ANALISIS PEMBERDAYAAN PEREMPUAN UNTUK MENUNJANG EKONOMI KELUARGA MELALUI KELOMPOK ASHOKA DI DUSUN PANTAI SELATAN DESA PENJALAAN KABUPATEN KAYONG UTARA - Rafikah, Rafikah; Rustiyarso, Rustiyarso; Ramadhan, Iwan (Universitas Tanjungpura, 2024)
This research aims to determine the output, income and impact of empowering women to support the family economy through the Ashoka group in Pantai Selatan Hamlet. The research employs a descriptive qualitative method. Data is gathered through observation, interviews, and documentation, utilizing tools such as observation guides, interview guides, and documentation. The data analysis involves techniques such as data reduction, presentation, drawing conclusions, and verification. Data validity is ensured through extended observations and triangulation. The research results show that the output of women's empowerment is to support the family economy, such as helping to finance daily life, children's education, meeting household needs, recreation and so on. The result (income) of women's empowerment is providing knowledge to members such as attending training, increasing sales income received, improving the quality of members in making products. The impact of empowering women to support the family economy is that it has a positive effect on society, especially women's groups, providing opportunities to increase the abilities and development of women's groups in making products.